Probability Density Function of Streamwise Velocity Fluctuation in Turbulent T-junction Flows. (May 2017) - Lin, Mei; Qiao, Xiaoyu; Yin, Yantao; Lin, Zhimin; Wang, Qiuwang
Abstract: The streamwise velocity time series are measured at the centreline of T-junction channel with aid of the hot wired anemometry. The probability density function (PDF) of the velocity fluctuation has been investigated under different cross velocities and velocity ratios. The PDF is almost Gaussian at the center of the cross tube. Whereas for the other normal locations, y /w≤0.14, the PDF are negatively skewed with sub-Gaussian distributions in the high speeds. Meanwhile they are independent of the cross velocity and velocity ratio. In contrast, the streamwise velocity fluctuation is highly intermittent in the low speeds and they are dependent of the velocity ratio.